Microstructures and hydrogen storage properties of as-cast and copper-mould-cast LaMg4Ni alloys - 范燕平 彭显云 刘宝忠 宿太超 哈日巴拉 (Journal of rare earths, 2014)
Phase compositions, morphologies and hydrogen storage properties of the as-cast and copper-mould-cast LaMgaNi alloys were studied. The dehydriding onset temperature of the as-cast alloy hydride was about 500 K, which was at least 50 K higher than that of the copper-mould-cast one, and the copper-mould-cast alloy hydride had a faster dehydriding rate compared with as-cast one. Additionally, the copper-mould-cast alloy could uptake 2.85 wt.% hydrogen, which was 95.0% of saturated hydrogen storage capac- ity at room temperature. While only 1.80 wt.% hydrogen （60% of saturated capacity） was absorbed for the as-cast alloy under the same conditions. The reversible hydrogen storage capacities and plateau hydrogen pressures of the two alloys were close. X-ray dif- fractions and scanning electron microscopy results indicated that similar thermodynamic property of the two alloys should be ascribed to the same hydrogen storage phase, Mg and MgzNi. The better hydrogen sorption kinetics of copper-mould-cast alloy should be as- cribed to the more uniform phase distribution compared with that of the as-cast one.